2014
DOI: 10.1111/jtxs.12063
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and Nuclear Magnetic Resonance Study on Heat‐Induced Gel Properties of Spent‐Hen Myofibrillar Protein Affected by Porcine Plasma Protein

Abstract: Model heat-induced gels were prepared. Compared with the broiler myofibrillar protein (BMP), interactions between porcine plasma protein (PPP) and spent-hen myofibrillar protein (SHMP) were evaluated using rheology, textural analysis, nuclear magnetic resonance and scanning electron microscopy (SEM). The gel hardness of SHMP was higher than that of BMP. PPP had the highest stickiness and immobilized water fraction of all the gels. The plasma and broiler myofibrillar mixed proteins had a storage modulus similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…In addition, interaction of ultrasound with hydrophobic groups and exposure of amino acids and carboxyl groups can contribute to the decrease in the absolute potential [73] . Notably, Zhang et al [74] reported that appropriate ultrasound energy increased the absolute value of zeta potential in commercial broilers, but when ultrasound energy was too high (500 W), absolute value of zeta potential decreased.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, interaction of ultrasound with hydrophobic groups and exposure of amino acids and carboxyl groups can contribute to the decrease in the absolute potential [73] . Notably, Zhang et al [74] reported that appropriate ultrasound energy increased the absolute value of zeta potential in commercial broilers, but when ultrasound energy was too high (500 W), absolute value of zeta potential decreased.…”
Section: Resultsmentioning
confidence: 99%